(3HMhK GdJShjb eONd JWHjbj daYGdjI GdbQGQGJ GdJShjbjI (B/s - (3GdUMf, eMeO aQjOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI ddfTQ(B, s, 2001)
(3eaghe hCgejI HMhK GdJShjb , HMhK GdJShjb haYGdjI GdbQGQGJ GdJShjbjI , CfhGY HMhK GdJShjb heLGdGJ JWHjbGJgG , GdefgL GdYdej aj HMhK GdJShjb , GdHjGfGJ hOhQgG aj HMhK GdJShjb , CSGSjGJ hCfhGY GdeYGjfI hESJNOGeGJgG aj HMhK GdJShjb , GdbjGS hGdYdGbGJ GdjHjI aj HMhK GdJShjb EYOGO bhGFe GdESJbUGA , GdaQhV GdYdejI EYOGO GdJbGQjQ(B.s
Keywords: (3GdJShjb(B-(3GdHMhKs